2011
DOI: 10.1590/s1679-87592011000500014
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of methods for estimating fish assemblages associated with estuarine artificial reefs

Abstract: A B S T R A C TMonitoring strategies which adequately represent the entire community associated with artificial structures will enable more informed decisions regarding the broader effects of artificial structures and their role in the management of fisheries resources. Despite the widespread application of a range of in situ visual monitoring methodologies used in the assessment of artificial structures, the relative biases associated with each method have not been critically examined and remain poorly unders… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…The CI of S B was higher than that of S AR+Re , showing that ARs can shorten and modify the food web and increase net production. Claudet & Pelletier (2004) and Lowry et al (2011) reported higher biomasses in reef areas than in areas without reefs, with reef areas supporting large numbers of fish. Pitcher et al (2002) utilized Ecopath to simulate the marine ecosystem of Hong Kong and investigate the relationship between reef fish biomass and the relative size of ARs inside marine protected areas (AR/MPA).…”
Section: Ar Deployment Contributed To the Maturity Of The Improved Ecosystemmentioning
confidence: 96%
See 1 more Smart Citation
“…The CI of S B was higher than that of S AR+Re , showing that ARs can shorten and modify the food web and increase net production. Claudet & Pelletier (2004) and Lowry et al (2011) reported higher biomasses in reef areas than in areas without reefs, with reef areas supporting large numbers of fish. Pitcher et al (2002) utilized Ecopath to simulate the marine ecosystem of Hong Kong and investigate the relationship between reef fish biomass and the relative size of ARs inside marine protected areas (AR/MPA).…”
Section: Ar Deployment Contributed To the Maturity Of The Improved Ecosystemmentioning
confidence: 96%
“…They can influence nutrient cycling and transport (Falcão et al 2007, Vicente et al 2008 and sediment biogeochemistry (Alongi et al 2008), with subsequent changes in community structure and richness of associated organisms (Langlois et al 2006). Lowry et al (2011) reported higher fish biomasses in reef areas compared to areas without reefs, with reef areas supporting larger numbers of fish. Although quantitative assessments of artificial ecosystems including ARs have been performed in Li Island, Rongcheng City, China (Wu et al 2016) and Zhangzi Island, Dalian City, China (Z. , few studies have compared ecosystem status before and after AR deployment.…”
Section: Introductionmentioning
confidence: 99%
“…Although bias by observer presence is reduced or entirely eliminated, the moving object of the STAVIRO apparatus might still alter fish behaviour (Mallet, Wantiez, Lemouellic, Vigliola, & Pelletier, 2014). The often-used Baited-Remote Underwater Video (BRUV) technique involves video surveillance of bait, which is placed in a particular habitat (Lowry, Folpp, Gregson, & Mckenzie, 2011;Unsworth, Peters, McCloskey, & Hinder, 2014). The resulting footage is then used to estimate fish abundance.…”
mentioning
confidence: 99%
“…Fish ethology, a discipline concerned with exploring the movement, behaviours and activities of either wild or cultivated fish under natural conditions, has shown great prospects in aquaculture, fisheries, and other marine related surveys and applications [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional studies mainly focus on in situ observations periodically conducted by marine biologists, which are time consuming and dependent on strict knowledge and the ability to observe, count and describe [3][4][5][6][7][8]. Underwater vision systems, either tethered to a vessel or a shore-based facility, or operated by remotely operated vehicles (ROV) and autonomous underwater vehicles (AUV), have increased rapidly over the last decade [9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%